2020
DOI: 10.1111/eje.12584
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of assessment feedback in preclinical dental education

Abstract: Introduction Development of evaluative judgement abilities through assessment and feedback strategies is crucial in students’ progress to become self‐regulated lifelong learners. Dentists’ ability to appraise the quality of treatment provided to their patients starts with development of competences in a simulated preclinical training environment. However, the effectiveness of these assessment and feedback strategies is not well understood. Material and methods This literature review aimed to identify the asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In our study, a vast majority of subjects were more satisfied with interactive form of teaching like problem based lectures, interactive lectures, small group teachings etc. Results similar to our study have also been reported in previous studies (10)(11)(12)(13). The reason could be that interactive teaching methods involve bilateral communication, which plays a very important role in enhancing student's interest during the lectures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, a vast majority of subjects were more satisfied with interactive form of teaching like problem based lectures, interactive lectures, small group teachings etc. Results similar to our study have also been reported in previous studies (10)(11)(12)(13). The reason could be that interactive teaching methods involve bilateral communication, which plays a very important role in enhancing student's interest during the lectures.…”
Section: Discussionsupporting
confidence: 92%
“…The student feedback is very important in providing information to the teacher regarding the effectiveness of various teaching methods. This information can be useful for the teacher to bring about modifications in their teaching strategies so as to improve the quality of education (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The included articles in this review demonstrate the relative paucity of utilization and impact of feedback within the pharmacy education literature. Much of what is known about feedback and how to provide feedback in pharmacy, dental, and medical education is based on little to no high-quality evidence, thus evidence-based recommendations are lacking [ 9 , 80 ]. A recent systematic review of feedback within nursing education, however, found quality feedback as described by students to be timely, incorporate positive and constructive comments, be directly related to the content, linguistically clear, and feed forward or justify a grade [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…As more evidence accumulates that demonstrates many of the skills and competencies carried into professional practice are first developed in the educational setting, reviews, assessments, and feedback of preclinical dental education regarding important, but often overlooked, healthcare issues such as DV and IPV become more imperative [ 44 , 45 ]. The function of educational research in the assessment and evaluation of this type of training in the context of public health, particularly for healthcare students with areas of specialty that may be uniquely suited to finding, reporting, treating, and referring patients at risk for DV and IPV, has also become evident [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%